2019
DOI: 10.1159/000503845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycerol Test on Resonance Frequency in Patients with Ménière’s Disease

Abstract: Objective: To evaluate resonance frequency (RF) values via dehydration effects in the inner ear caused by the glycerol test, which is used as a diagnostic method for Ménière’s disease (MD). Methods: Twenty adult patients with unilateral MD were included in the study. Before, and then at 1, 2, and 3 h after administration of glycerol (1 g/kg), pure-tone hearing levels (125–8,000 kHz) and multifrequency tympanometry tests were performed. As a control, the RF values of the ears of 25 healthy subjects (i.e., 50 ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The two groups seem to be comparable regarding RF (Mdiff = −42.5, 95% CI: [−102.5]–[17.4], I 2 = 0.66%). The same measurement between affected ears and control ears was also reported in four studies [ 27 , 28 , 30 , 31 ] with a total of 521 ears (AE n = 205, CE n = 316). The results show no statistically significant differences between the two groups (Mdiff = −106.6, 95% CI: [−219.3]–[6.0], I 2 = 77%).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The two groups seem to be comparable regarding RF (Mdiff = −42.5, 95% CI: [−102.5]–[17.4], I 2 = 0.66%). The same measurement between affected ears and control ears was also reported in four studies [ 27 , 28 , 30 , 31 ] with a total of 521 ears (AE n = 205, CE n = 316). The results show no statistically significant differences between the two groups (Mdiff = −106.6, 95% CI: [−219.3]–[6.0], I 2 = 77%).…”
Section: Resultssupporting
confidence: 66%
“…Ultimately, seven studies reported a total of 899 ears, 282 of which were affected by Ménière’s disease, 197 were unaffected ears, and 420 were control ears. Four of them were conducted in Japan [ 26 , 27 , 28 , 29 ], one of them in France [ 30 ], and one in Turkey [ 31 ] and the Netherlands, respectively [ 32 ]. All seven studies had a prospective cohort design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not analyse the RF in our population since previous results are very conflicting. Moreover, the RF decreased during the glycerol test in a study by Oz et al from 2019[Oz et al, 2019. The glycerol test is a dehydration test used in the diagnosis of MD.…”
Section: Discussionmentioning
confidence: 95%
“…RF is the frequency with the lowest resistance and the highest vibration of the middle ear system and is affected by changes in mass and hardness occurring in the middle ear mechano-acoustic system. 6 …”
Section: Introductionmentioning
confidence: 99%